Students’ Truth-Seeking Behaviour in Solving Problems with No Specified Universal Set Given - Rahmawati, Mira; Kurniati, Dian; Trapsilasiwi, Dinawati; Osman, Sharifah (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2021)
The truth-seeking behaviour of students is the main predictor of someone having critical thinking behaviour. Therefore, it is necessary to conduct research related to students' seeking behaviour in responding to mathematical problems. The purpose of this study was to describe the truth-seeking behaviour of students in working on problems with an unknown universe based on the IDEAL problem-solving model. This research was a qualitative descriptive study, with the stages were (1) determining the research subject, (2) making instruments, (3) giving questions to the subject and recording truth-seeking behaviour, (4) analyzing data, (5) triangulating between observations and interviews. interviews, and (5) conclusions. The results of this study are students tend not to behave truth-seeking in working on problems with an unknown universe based on the IDEAL model. However, students did the steps contained in the IDEAL model, although they did not use all the existing stages. In addition, students tend not to give conclusions that are in accordance with the purpose of the question after working on the problem.Perilaku truth-seeking siswa merupakan prediktor utama seseorang memiliki perilaku berpikir kritis. Oleh karena itu, perlu dilakukan penelitian yang berkaitan dengan perilaku trth-seeking siswa dalam merespon permasalahan matematika. Tujuan penelitian ini adalah mendeskripsikan perilaku truth-seeking yang dimiliki oleh siswa dalam mengerjakan soal dengan semesta yang tidak diketahui berdasarkan model pemecahan masalah IDEAL. Penelitian ini merupakan penelitian deskriptif kualitatif, dengan tahapan (1) penentuan subjek penelitian, (2) pembuatan instrumen, (3) pemberian soal kepada subjek dan perekaman perilaku truth-seeking, (4) penganalisisan data, (5) triangulasi antara hasil pengamatan dan wawancara, dan (5) penyimpulan. Hasil dari penelitian ini adalah siswa cenderung tidak berperilaku truth-seeking dalam mengerjakan soal dengan semesta yang tidak diketahui berdasarkan model IDEAL. Tetapi, siswa melakukan tahap-tahap yang terdapat di dalam model IDEAL, meskipun tidak menggunakan semua tahapan yang ada. Selain itu, siswa cenderung tidak memberikan kesimpulan yang sesuai dengan tujuan soal setelah mengerjakan soal tersebut.